Impaction of Permanent Canine due to Retaining of Deciduous Teeth - Nessa, Jebun; Akter, Mahmuda; Hasan, Md Kamrul (Medicine Today, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> In our daily practices some of the dental problems are ignored but bears a signaficant role. People meet dentist until it becomes very serious and creating problem in our daily works. The case we are going to discuss that ignored at patients childhood but now its a burning issue for her. This case dealt at dental out patient depertment of Banghabandhu Sheikh Mujib Medical University, Dhaka. 24 years old female - Miss Ema Ghosh presented with discharging sinus through the space between upper right lateral incisor and 1st premolar due to infection of remaining root portion of deciduous canine for one month. Resulting from this retaining root portion of deciduous tooth the permanent canine became impacted. Key words: Impacted canine; BDR; OPG. DOI: 10.3329/medtoday.v22i1.5609 Medicine Today Vol.22(1) 2010. 53-54